The right of information as a restriction on the penal protection of individual right of privacy - Mokrane, Abderrezak (Journal of Human Sciences, 2020)
The development of information and communication technology has given rise to the enlargement of the framework of the information liberty to the detriment of one of the most sensitive right, which is privacy right. The right of information has become such a pretext to attain people’s images, privacy discussions, without permission, specially in social media. That’s why the Algerian legislator has been obliged to intervene by deciding a penal protection of privacy right. However, in an other hand, the journalist may has reasons relative with the practice of his functions which are informing people in application of information right. so, and in front of this collision between privacy right and right if information, it was necessary to equilibrate the two rights to achieve a strict information without outrage to people’s privacy right.